A history of economic thought - Bell, John Fred (New York (N.Y.) : Ronald Press, 1953)
Pt. 1. The beginnings of economics - pt. 2. The beginnings of modern theoretical and applied economics - pt. 3. The development of classical economics - pt. 4. Critics and criticisms if classical economics - pt. 5. The development of economics in the United States - pt. 6. The development of economics in the United States - pt. 7. The main currents of economic thought in the twentieth century